Functional and Structural Annotation of Uncharacterized Lysine Methyltransferase Proteins in Candida auris - Himanshu Kishore Prasad (Proceedings)
Candia auris is a fungal pathogen that has emerged as a global threat in recent years due to its resistance to multiple antifungal drugs and its ability to cause invasive infections, especially in immunosuppressed patients [...]